(untitled) (International Seven Journal of Health Research, 2023)
Pregnancy commonly represents a watershed in a woman’s life, uncertainty with the conduct of the pregnancy is perhaps the most critical point of pregnancies characterized as high risk. Thus, there is a need to analyze the rates of high-risk pregnant women assisted in the Family Health Strategy (ESF) and their associated comorbidities, to devise strategies that reduce possible complications and provide health education. Objective: To determine the epidemiological profile of high-risk pregnant women in the area covered by an ESF. Justification: The collection of these data can be used as a screening tool for the main comorbidities in high-risk pregnant women, enabling action planning. Method: Descriptive cross-sectional study with a quantitative approach carried out by students of the medical course in a supervised internship that reviewed records of all pregnant women attended from January 2020 to November 2022, in an ESF in the city of Blumenau, Santa Catarina, Brazil. In reviewing the records, the following variables were verified: age, gynecological and obstetrical history, pathologies prior to pregnancy and current pathologies. Results: In the studied sample of 71 pregnant women, high-risk pregnancy affected more women between 21 and 25 years old, pointing out as main associated comorbidities, respectively, hypertensive disease, diabetes, thyroid alterations and gestational syphilis. Conclusion: The main associated comorbidities can be optimized and prevented during prenatal follow-up in the ESF. In this sense, the ESF would make a difference in the life of this population as support groups for high-risk pregnant women were created, serving both as an environment for awareness and support and tracking of the most common comorbidities in pregnancies in the area covered by each ESF. The practice suggested in this type of activity would include round tables with an adequate number of pregnant women for the needs of each unit; During these meetings, the services of a multidisciplinary team would be available: nutritionist, physical educator, physiotherapy, psychology, with the aim of making future mothers aware of why they are being classified as "high risk", and how best to address their condition, or by changes in lifestyle related to physical activity and dietary re-education, as examples.